2012
DOI: 10.4236/ojmp.2012.11001
|View full text |Cite
|
Sign up to set email alerts
|

Continued Successful SA Recovery during the Maintenance Stage: Intra-Individual Resource Loss & Gain Predict Relapse

Abstract: Objectives We combine Hobfoll’s Conservation of Resources (COR) theory and key components of self-help group “step work” ideology to investigate how dynamic changes in key intra-individual resource loss and gains (self-esteem, abstinence self-efficacy, existential growth) influence relapse rates in a sample of individuals in the Maintenance Stage of substance abuse recovery. Methods Participants (n = 579) completed two surveys over a nine month period that assessed baseline and changes in intra-individual lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, past studies have pointed to the importance of individual change being the best predictor of individual outcomes over time (Chavarria, Stevens, Jason, & Ferrari, 2012). Walt, Stevens, Jason, and Ferrari (2012) found that steady improvement in personal gain scores (e.g., self-esteem, abstinence self-efficacy) over time predicted lower relapse rates. Our study provides more support for integrative models that illustrate this dynamic effect of resource loss and gain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, past studies have pointed to the importance of individual change being the best predictor of individual outcomes over time (Chavarria, Stevens, Jason, & Ferrari, 2012). Walt, Stevens, Jason, and Ferrari (2012) found that steady improvement in personal gain scores (e.g., self-esteem, abstinence self-efficacy) over time predicted lower relapse rates. Our study provides more support for integrative models that illustrate this dynamic effect of resource loss and gain.…”
Section: Discussionmentioning
confidence: 99%
“…This recovery factor improvement protects residents from a premature exit from the OH during the high-risk period when most evictions occur. Prior studies have also found positive recovery outcomes among Black and Latinx residents of OH 8 10 . It appears that people of color are able to create or access resources better than White residents when living in recovery homes, 11 but the reasons for this differential outcome are not known.…”
Section: Introductionmentioning
confidence: 98%
“…Prior studies have also found positive recovery outcomes among Black and Latinx residents of OH. [8][9][10] It appears that people of color are able to create or access resources better than White residents when living in recovery homes, 11 but the reasons for this differential outcome are not known.…”
Section: Introductionmentioning
confidence: 99%